Selective caffeine removal from green tea using supercritical carbon dioxide extraction - Kim, Wan-Joo; Kim, Jae-Duck; Kim, Jaehoon; Oh, Seong-Geun; Lee, Youn-Woo (ELSEVIER SCI LTD, 2008)
Caffeine and EGCG (epigallocatechin gallate) were extracted from green tea using supercritical carbon dioxide (SCCO2) with water as a cosolvent. Experimental conditions were carefully chosen to selectively extract a large amount of caffeine from the green tea while to remain a large amount of EGCG in the green tea. Various experimental conditions were explored including temperatures ranging 40-80 degrees C, pressure ranging 200-400 bar, and water contents ranging 4-7 wt%. At 40 degrees C, 400 bar and the water content of 7 wt%, the caffeine extraction yield was 54% while the EGCG extraction yield was 21%, resulting in caffeine/EGCG extraction selectivity of 2.57. The larger caffeine extraction yield agreed well with estimation of solubility parameter differences between SCCO2/water and caffeine/EGCG. The extraction results using SCCO2/water were compared with conventional liquid solvent extraction using water or ethanol. The selectivity of caffeine/EGCG extraction with water was 0.88 and the selectivity of caffeine/EGCG extraction was 0.24 with ethanol. Thus SCCO2 extraction with water as a cosolvent is suitable for the selective extraction of caffeine from the green tea. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: FLUID EXTRACTION; RETROGRADE CONDENSATION; CAMELLIA-SINENSIS; CATECHINS; POLYPHENOLS; WATER; CONSUMPTION; SOLUBILITY